Okay, same principle as last time.
Solve for y in the easier equation (x-2y=1)
x-2y=1
x=1+2y
Now we have a value that we can plug into the other equation.
x^2+y^2=10
Plug in x
(1+2y)^2+y^2=10
Expand
1+4y+4y^2+y^2=10
Combine like terms (in this case y^2)
5y^2+4y+1=10
Now bring the 10 over by subtracting 10 on both sides
5y^2+4y-9=0
Factor this equation
(5y+9)(y-1)=0
Since one of these factors must be zero for the whole thing to equal 0,
y=1 and -9/5
Plug each one into the other equation:
x-2y=1
x-2(1)=1
Simplify and solve
x-2=1
x=3
BUT, we have the other solution so you need to plug that one in as well.
x-2y=1
x-2(-9/5)=1
x+18/5=1
Subtract 18/5 from both sides
x=1-18/5
x=5/5-18/5
x=-13/5=-2.6
x=3 and -2.6 or -13/5
y=1 or -9/5
Those are your two answers.
Hope this helps.
Note: the y=1 is paired with the x=3 (3,1) and the y=-9/5 is paired with the x=-13/5 (-9/5, -13/5)
2006-11-28 05:01:15
·
answer #1
·
answered by Aegor R 4
·
0⤊
1⤋
x² + y² = 10- - - - - -Equation 1
x - 2y = 1- - - - - - - Equation 2
- - - - - - - -
Substitute method equation 2
x - 2y = 1
x - 2y + 2y = 1 + 2y
x = 1 + 2y
The answer is x = 1 + 2y
Insert the x value into equation 1
x² + y² = 10
(1 + 2y)² + y² = 10
(1 + 2y)(1 + 2y) = 1 + 2y 2y + 4y² = 1 + 4y + 4y²
1 + 4y + 4y² + y² = 10
1 + 4y + 5y² = 10
1 + 4y + 5y² - 10 = 10 - 10
4y + 5y² - 9 = 0
(5y + 9)(y - 1) = 0
y = 1
Y = - 9/5
Insert the y value into equation 2
- - - - - - - - - - -
x - 2y = 1
x - 2(1) = 1
x - 2 = 1
x - 2 + 2 = 1 + 2
x = 3
The answer x = 3
Insert the x value into equation 1
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
x = 2y = 1
3 - 2(1) = 1
3 - 2 = 1
1 = 1
- - - - - - - - - - -
Check for equation 1
x² + y² = 10
(3)² + (1)² = 10
9 + 1 = 10
10 = 10
- - - - - - - - - - - - -
The solution set is { 1, 3 }
or
The solution set is (1, - 1.8)
The y value of y = - 9/5 works
- - - - - - - s-
2006-11-28 13:43:09
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
1⤋
x^ 2+y^2=10
x-2y=1
x = 2y + 1
plug x into the first equation
(2y+1)^2 + y^2 = 10
4y^2 + 4y + 1 + y^2 = 10
5y^2 + 4y - 9 = 0
use the quadratic equation
a = 5
b = 4
c = -9
y = 1, -1.8
x-2y=1
x - 2(1) = 1
x = 3
x - 2y = 1
x - 2(-1.8) = 1
x = 4.6
ANSWER
(4.6, -1.8)
(3, 1)
2006-11-28 13:03:14
·
answer #3
·
answered by trackstarr59 3
·
0⤊
1⤋
Okay, now you may do your own homework. I already helped you with one problem, now you can go through and actually try for yourself. This level of math is extremely easy and these problems should take you about a minute. If you need help, as your teacher for some review problems, or before school help. Getting answers from people online will never truly teach you unless you try for yourself.
2006-11-28 12:59:45
·
answer #4
·
answered by sft2hrdtco 4
·
0⤊
1⤋